2016
DOI: 10.1519/jsc.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Two Different Resistance Circuit Training Protocols on Performance and Perceived Exertion in Semiprofessional Basketball Players

Abstract: This study aimed to investigate the acute effects of two different resistance circuit training protocols on basketball players' physical and technical performance and rating of perceived exertion (RPE). In a repeated-measures, crossover experimental design, 9 semiprofessional basketball players performed a Power Circuit Training (PCT; 45% 1RM) and a High-Resistance Circuit Training (HRC; 6RM), on consecutive weeks. Vertical and horizontal jump performance, 3-points shooting accuracy, repeated-sprint ability (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
3
24
0
2
Order By: Relevance
“…RCBT is an effective training method for the concurrent development of maximum oxygen consumption (VO 2max ) and one repetition maximum (1-RM) bench press in healthy adults, independent of participant and load characteristics, as shown in the authors' review and meta-analysis [16]. Therefore, some forms of home-based RCBT could easily be performed with simple equipment at home and promote both neuromuscular and metabolic adaptations, thus minimizing neuromuscular detraining effects [17].…”
Section: Detraining Effects In Isolationmentioning
confidence: 99%
“…RCBT is an effective training method for the concurrent development of maximum oxygen consumption (VO 2max ) and one repetition maximum (1-RM) bench press in healthy adults, independent of participant and load characteristics, as shown in the authors' review and meta-analysis [16]. Therefore, some forms of home-based RCBT could easily be performed with simple equipment at home and promote both neuromuscular and metabolic adaptations, thus minimizing neuromuscular detraining effects [17].…”
Section: Detraining Effects In Isolationmentioning
confidence: 99%
“…The effect of fatigue on three-point shooting has been investigated from a biomechanical point of view analyzing the position of the release arm and shoulder girdle showing that all the measured angles decreased drastically as a consequence of the heavy level of fatigue ( Erculj & Supej, 2009 ). Three point-shooting accuracy has also been investigated after two different resistance circuit training protocols showing a reduction in accuracy only after the most intensive protocol ( Freitas et al, 2016 ). Conversely, free throw shooting analysis demonstrated that fatigue did not affect kinematics and that shooting technique was the same during successful and unsuccessful shots ( Uygur et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The generalization of experimental data allows us to conclude that it is advisable to apply the sets of circuit training for athletes at different stages of readiness. This approach is effective in basketball [19][20]. Currently, the volume of training and competitive loads has increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Circuit training sets are widespread in sports, among schoolchildren and overweight people [15][16][17][18]. In basketball, there are studies that confirm the effectiveness of the circuit training applying in the training process [19,20].…”
Section: Introductionmentioning
confidence: 99%